Combination of Syzygium cumini (L) Skeels seed extract with acetic acid to control Escherichia coli on mint (Mentha cordifolia opiz.) leaves - Sumate Tantratian; Warawut Krusong; Orawan Siriwetwut (LWT, 2022)
Four extraction methods were applied to extract phenolic compounds from Syzygium cumini seeds (SCS) with 50% ethanol solution. The microwave-assisted extraction provided the extract with highest yield and highest total phenolic and total flavonoid concentration which followed by ultrasonic-assisted extraction. The high-temperature and ambient extractions with a shaker provided no difference (p ≥ 0.05) in phenolic and flavonoid content. The HPLC analysis of SCS extracts illustrated gallic acid as the main component. The extract demonstrated a bactericidal effect against Escherichia coli at 6.25 mg ml−1. Mint leaves were found to carry high number of total viable count (TVC) and E. coli. The leaves soaked in acetic acid (AA) demonstrated a reduction of microbial number, but dark spot defect was found. Soaking in the mixture of 4.68 mg ml−1 SCS extract and 0.39 mg ml−1 AA caused the number of TVC and E. coli to reduce by 1.8 and 1.3 log10 CFUg−1, respectively, while black spot was not detected. Nine day storage leaves showed satisfactory level of microbial quality and fresh-liked appearance. This demonstrated the potential application of SCS extract with AA as a synthetic substitute for microbial control on fresh leaf vegetables.
Keywords: Essential Oils and Antimicrobial Activity; Phytochemicals and Antioxidant Activities; Phytochemistry and Biological Activities